Machiavelli versus Concave Utility Functions: Should Bads Be Spread out or Concentrated? - Paul Frijters; Christian Krekel; Aydogan Ulker (Institute of Labor Economics (IZA), 2020)
Is wellbeing higher if the same number of negative events is spread out rather than bunched in time? Should positive events be spread out or bunched? We answer these questions exploiting quarterly data on six positive and twelve negative life events in the Household, Income and Labour Dynamics in Australia panel. Accounting for selection, anticipation, and adaptation, we find a tipping point when it comes to negative events: once people experience about two negative events, their wellbeing depreciates disproportionally as more and more events occur in a given period. For positive events, effects are weakly decreasing in size. So both the good and the bad should be spread out rather than bunched in time, corresponding to the classic economic presumption of concave utility rather than Machiavelli's prescript of inflicting all injuries at once. Yet, differences are small, with complete smoothing of all negative events over all people and periods calculated to yield no more than a 12% reduction in the total negative welbeing impact of negative events.
Keywords: D1; I31; K0; 330; wellbeing; mental health; life events; non-linearities; hedonic adaptation; welfare analysis